Organizzazione spaziale dei gesti semilinguistici nelle comunicazioni italiana e polacca - Szarota, Beata (Studia Romanica Posnaniensia, 2007)
The term o f rhetoric has known several senses since its foundation as techne o f persuasion by Aristote. This paper presents the historical reasons o f limitation o f the first rhetorical project into the scholar treaties in n ^ - l i ) 111 centuries. The next question is to explain the revival o f rhetorical tradition with Chaim Perelman Olbrechts-Tyteca Traite de ¡’argumentation focused on the theory o f argumentation and the French “nouvelle critique” focused on linguistics and stylistics. The key-term for both linguistic and philosophic approach o f new rhetoric is a figure o f speech. The author tries to find out if the modern reunified vision o f rhetoric is possible and suitable.